(untitled) (International Journal of Engineering and Computer Science, 2015)
The extensible markup language XML has recently to come into view as a new standard for information representation and exchange on the internet. With XML becoming ever-present language for data interoperability purposes in various domains, efficiently querying XML data is a critical issue. XML has become a practice standard to store, share and exchange business data across similar and dissimilar platforms. The interoperability is possible though XML. As organizations are generating large amount of data in XML format, there is a need for processing XML tree pattern queries. This paper presents survey on some developments in the field of XML tree pattern query processing, especially focusing on holistic approaches. XML tree pattern query processing is a research flow within XML data management that focuses on efficient Tree Pattern Query (TPQ) answering. The existing holistic algorithms for XML tree pattern matching queries display suboptimmality problem as they consider intermediate results before taking final results. This causes suboptimal performance. This suboptimality is overcome by using TreeMatch algorithm. This paper presents the overview of prototype application that makes use of efficient Dewey labeling scheme to overcome suboptimality with TreeMatch algorithm.